Nurse workload and caring behavior in emergency department and intensive care unit - Kurniasih, Yuni; Farida, Anis (International Journal of Health Science and Technology, 2024)
The intensive care unit or ICU (Intensive Care Unit) and the Emergency Department are units that provide relatively nursing services that require a high level of skill due to the patient's condition requiring quick and precise treatment. Objective: To determine the relationship between nurse workload and the caring behavior of nurses in the Emergency Room (IGD) and Intensive Care Unit (ICU) of PKU Muhammadiyah Gamping Hospital. Method: This research uses quantitative research with a correlation method with a cross-sectional time approach. The sampling technique uses total sampling. The sample in this study was 43 respondents, namely nurses who served in the Emergency Room (IGD) and Intensive Care Unit (ICU) of PKU Muhammadiyah Gamping Hospital. Results: The results of research using the Spearman-Rank test showed that there was a significant relationship between nurse workload and caring behavior of nurses in the Emergency Room (IGD) and Intensive Care Unit (ICU) of PKU Muhammadiyah Gamping Hospital (p-value 0.022 < 0.05). The closeness of the relationship with the significance value τ = -0.349 (sufficient correlation). Conclusions and Suggestions: From the results of this study, it was found that there was a relationship between nurses' workload and the caring behavior of nurses in the Emergency Room (IGD) and Intensive Care Unit (ICU) of PKU Muhammadiyah Gamping Hospital. Respondents should be able to use their rest time well so that it does not result in excessive fatigue.